Screening of Antibodies to hepatitis B virus core Antigen (Anti Hbc total) in negative HBs - Ag blood units - يازجي, هيثم; زريق, يوسف; صقر, إياد (Latakia University Journal -Medical Sciences Series, 2020)
A total of 90 negative anti-HBs blood samples were collected from Tishreen University Hospital Blood Bank in Latakia, Syria. Blood units were selected randomly regardless of age, gender and blood group. The samples were taken into anticoagulant tubes, the appropriate centrifugation was performed for each sample and blood plasma was obtained. The competitive enzymatic immunoassay method (ELISA) was used by the appropriate kit to detect the presence of total HBc antibodies, since antibodies to HBc antigen may be the only marker of recent virus infection (Window Period) and also with some chronic carriers or due to mutations in virus, without necessarily being positive for HBs antigen. The results showed nine positive samples for total HBc antibodies. which represent 10% of the all tested samples. This is of critical diagnostic and medical importance to detect these antibodies in blood donors along with the HBs antigen, in order to increase the level of safety and to reduce the risk of hepatitis B infection through blood transfusion, as Blood Transfusion Centers in Syria investigate only the HBS antigen in blood donors to exclude the transmission of HBV infection through blood transfusion.